Hepatitis B virus evades innate immunity of hepatocytes but activates cytokine production by macrophages. Issue 6 (20th November 2017) - Cheng, Xiaoming; Xia, Yuchen; Serti, Elisavet; Block, Peter Daniel; Chung, Michelle; Chayama, Kazuaki; Rehermann, Barbara; Liang, T. Jake
Abstract : Hepatitis B virus (HBV) infects hepatocytes specifically and causes immune‐mediated liver damage. How HBV interacts with the innate immunity at the early phase of infection, either with hepatocytes or other cells in the liver, remains controversial. To address this question, we utilized various human cell‐culture models and humanized Alb‐uPA/SCID mice. All these models were unable to mount an interferon (IFN) response despite robust HBV replication. To elucidate the mechanisms involved in the lack of IFN response, we examined whether HBV actively inhibits innate immune functions of hepatocytes. By treating HBV‐infected cells with known inducers of the IFN signaling pathway, we observed no alteration of either sensing or downstream IFN response by HBV. We showed that the DNA innate sensing pathways are poorly active in hepatocytes, consistent with muted innate immune recognition of HBV. Upon exposure to high‐level HBV, human macrophages could be activated with increased inflammatory cytokine expressions. Conclusion : HBV behaves like a "stealth" virus and is not sensed by, nor actively interferes with, the intrinsic innate immunity of infected hepatocytes. Macrophages are capable of sensing HBV, but require exposure to high HBV titers, potentially explaining the long "window period" during acute infection and HBV's propensity to chronic infection. (Hepatology 2017;66:1779–1793)